The feature interaction problem: Automatic filtering of incoherences and generation of validation test suites at the design stage. - Gorse, Nicolas. (University of Ottawa (Canada), 2001)
This thesis addresses the feature interaction problem in the research area of telephone systems design. We start with a review of this problem and present our definition of a feature and of a feature interaction. We enumerate and discuss some known approaches with respect to their strengths and limitations. We present our initial approach and propose some refinements in order to automate the detection of incoherences and derivation of validation scenarios at the design stage using predicate logic and Prolog. The identification of incoherences corresponding to potential feature interactions allows the designer to refine the requirements and to produce a better specification. A UCM model is derived from requirements. This model allows the designers to have a general point of view of the system and to detect design defaults. The construction of the UCM model is followed by the generation of a LOTOS specification. The derivation of validation test suites and their application against the specification permits to check whether or not the incoherences identified in the requirements lead to feature interactions. The results obtained over two case studies show that the application of this approach improves the design and validation of a specification.
Keywords: Computer Science.